Faktor Fisik dan Biologi dengan Keluhan Sick Building Syndrome - Endah Aryadni; Juanda Juanda; Imam Santoso (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2018)
Abstract: Physical And Biology Factor with Sick Building Syndrome Subjective Complaint. One of disturbance health phenomenalism that linked to air quality is Sick Building Syndrome (SBS). SBS is symptom collections whom felt by employeer in a work room that linked to duration of work and air quality. This research used explanatory research by cross sectional approachment. Total population used to sample collection that count of 44 respondents. Research variable for unimpeded variables were temperature, humidity, illumination, amount of air bacteria, age, work duration per day and year of work whereas impeded variable was Sick Building Syndrome subjective complaint. Technical of data collection were measuring, observation and quiz. Data analyze method used univariat analyze with descriptive, and bivariat analyze with spearman’s rho correlation. Outcome of research showed that there were no relation between temperature with p value 0,716 > 0,05, humidity with p value 0,818 > 0,05, illumination with p value 0,529 > 0,05 and amount of air bacteria with p value 0,759 > 0,05 to SBS subjective complaint in office work room of RRI Banjarmasin.